Surface modification of materials using an extremely non-equilibrium oxygen plasma - Mozetič, Miran (Materiali in tehnologije, 2010)
Several technological processes based on the interaction of extremely non-equilibrium oxygen plasma are described. A plasma with a low kinetic temperature of heavy particles and an extremely high density of neutral oxygen atoms is created in glass plasma reactors by inductively coupled radio-frequency (RF) discharges. The density of the charged particles is kept low at around 1016 msup{-3}, while the density of the neutral oxygen atoms may exceed a value of 1 * 1022 msup{-3}. The neutral oxygen atoms are chemically active and readily react with solid materials, even at low temperatures. The interaction of the oxygen atoms with metal samples often causes a rapid nucleation of metal oxide isles and the spontaneous growth of one- or two-dimensional structures, such as nanowires and nanobelts. These "nanofeatures" are often monocrystalline. The exposure of different carbon-rich materials to an oxygen plasma is applied for the functionalization with oxygen functional groups as well as for the controlled oxidation of various materials. The superhydrophilicity of several polymers and composites can be achieved. The technique is suitable for the destruction of bacteria and thus the sterilization of delicate materials.
Keywords: nanotehnologija; plazma; kisik; oksidi; polimeri; sterilizacija